Binding of a potential anti-hepatoma drug cis, cis, trans-[Pt(NH3)2Cl2(O2CCH2CH2COOH)-(OCONHC16H33)] with serum albumin – thermodynamic and conformational investigations. (28th September 2015) - Qi, Li; Lu, Zhong; Lang, Wen-hua; Guo, Lu; Ma, Chang-geng; Sun, Guang-hong
Abstract : A potential anti-cancer compound with high activity was synthesized and its binding properties with human serum albumin were tested. Abstract : In this paper, a potential anti-hepatoma Pt 4+ drug cis, cis, trans -[Pt(NH3 )2 Cl2 (O2 CCH2 CH2 COOH)-(OCONHC16 H33 )] was synthesized and selected to investigate its binding to human serum albumin (HSA) by spectroscopy and molecular docking methods. Fluorescence spectra show that the Trp residue, the intrinsic fluorophore in HSA, was induced to a less hydrophobic microenvironment with the addition of the Pt 4+ compound, which induces the denaturation of HSA. Moreover, the fluorescence quenching mechanism was determined to be static quenching. The binding constant ( K A ) and the number of binding sites ( n ) were calculated based on the results of fluorescence measurements. Circular dichroism (CD), Fourier transform infrared spectroscopy (FTIR) and three dimensional fluorescence spectroscopy proved that the Pt 4+ compound could slightly change the secondary structure and induce unfolding of the polypeptides of protein. Thermodynamic parameters indicate that the Pt 4+ compound binds to HSA through electrostatic attraction with one binding site. The molecular docking study indicated that parecoxib is embedded into site I (subdomain IIA) of HSA.